2021
DOI: 10.1088/1757-899x/1098/5/052046
|View full text |Cite
|
Sign up to set email alerts
|

UI Zero Plastic as an action towards sustainable campus

Abstract: Plastic waste has become a globalized environmental issue. Indonesia became the second-largest producer of plastic waste after China based on a report from the World Economy Forum. Waste management and individual awareness of environmental issues are challenges for Indonesia. The more individuals who move, the more waste generation will result from these activities. University of Indonesia (UI) as an educational institution has more than 50,000 academic people/year and has diverse activities. UI produced 663,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is suggested that there are several areas for improvement such as the waste segregation process to improve the segregation process in the temporary waste area and to include waste evaluation as part of the complete cycle in waste management. The selected university have implementing environmental management system with different and comprehensive approach including UI Green Metric initiative [12,13], UI Zero plastics policy [18] and Safety, Health and Environmental management system [16,17]. Indeed, result from this research suggested that to encourage the implementation of waste management needs a strategy to achieve its environmental management system objectives, including the awards recognition program [9,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that there are several areas for improvement such as the waste segregation process to improve the segregation process in the temporary waste area and to include waste evaluation as part of the complete cycle in waste management. The selected university have implementing environmental management system with different and comprehensive approach including UI Green Metric initiative [12,13], UI Zero plastics policy [18] and Safety, Health and Environmental management system [16,17]. Indeed, result from this research suggested that to encourage the implementation of waste management needs a strategy to achieve its environmental management system objectives, including the awards recognition program [9,19].…”
Section: Discussionmentioning
confidence: 99%
“…It was found during the evaluation process that through the awards recognition program, faculties or schools or programs were more open in discussion, discuss the problems, provide feedback, deliver ideas on how to improve the waste management implementation, and improve institutional performance. Other studies have mention that providing awards for environmental management evaluation will create competitiveness in achieving environmental objectives and performance [2,7,11,15,18,19,22,23]. Indeed, participation of industry and government during the development of waste management evaluation process, increase the understanding, mutual benefit and better waste management implementation.…”
Section: Discussionmentioning
confidence: 99%